2013
DOI: 10.1111/nmo.12076
|View full text |Cite
|
Sign up to set email alerts
|

Vagus nerve stimulation: from epilepsy to the cholinergic anti‐inflammatory pathway

Abstract: The objective of this review was to explore the following: (i) the supporting evidence for the importance of VNS in epilepsy (and depression) and its mechanisms of action, (ii) the anti-inflammatory characteristics of the VN, (iii) the experimental evidence that VNS impact on inflammatory disorders focusing on the digestive tract, and (iv) how VNS could potentially be harnessed therapeutically in human inflammatory disorders such as inflammatory bowel diseases, irritable bowel syndrome, postoperative ileus, rh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
211
0
9

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 254 publications
(223 citation statements)
references
References 102 publications
(219 reference statements)
3
211
0
9
Order By: Relevance
“…VNS has been validated by the US Food and Drug Administration (FDA) for drug resistant epilepsy in 1997 and in 1994 for Europe and for depression in 2005. For these indications, the mechanism relies on an activation of vagal afferents by high frequency stimulation at 20-30 Hz (Bonaz et al, 2013). Indeed, low frequency stimulation is less efficient in epilepsy than high frequency stimulation and stimulation over 50 Hz induces damage of the VN (Schachter & Boon, 2007).…”
Section: Vagus Nerve Stimulation In Epilepsy and Depressionmentioning
confidence: 99%
See 2 more Smart Citations
“…VNS has been validated by the US Food and Drug Administration (FDA) for drug resistant epilepsy in 1997 and in 1994 for Europe and for depression in 2005. For these indications, the mechanism relies on an activation of vagal afferents by high frequency stimulation at 20-30 Hz (Bonaz et al, 2013). Indeed, low frequency stimulation is less efficient in epilepsy than high frequency stimulation and stimulation over 50 Hz induces damage of the VN (Schachter & Boon, 2007).…”
Section: Vagus Nerve Stimulation In Epilepsy and Depressionmentioning
confidence: 99%
“…Indeed, even low frequency VNS (1 Hz) discretely affected the level of c-fos expression in the rat NTS, compared to shamoperated animals (Osharina et al, 2006). Regarding the frequency of stimulation, if low frequency (5-10 Hz) is supposed to activate vagal efferents (Bonaz et al, 2013), we have reported in rats that even low frequency stimulation at 5 Hz was able to induce modifications of activation in the NTS, the first target of the VN in the brain, as well as in numerous areas of its brain projections (Reyt et al, 2010). Brain imaging studies in human as well as c-fos activation in the NTS and other NTS brain related nuclei have been reported in humans and animals under VNS respectively (Lomarev et al, 2002;Osharina et al, 2006).…”
Section: Questions-future For Vagus Nerve Stimulation In Inflammatorymentioning
confidence: 99%
See 1 more Smart Citation
“…This implant is under clinical trials to augment the oropharyngeal airway by stimulating the motor nerve and lowering the tongue in coordination with the breathing cycle [54,95]. Multiple mechanisms of action have been proposed to explain the various therapeutic effects of VNS, from emission of diffuse energy centrally towards the brain to disrupt the aberrant signals that contribute to uncontrolled epileptic seizures [13] to sympathetic and parasympathetic modulation of heart rate to prevent arrhythmia [32].…”
Section: Cuff Electrodesmentioning
confidence: 99%
“…The gut also possesses its own nervous system -the enteric nervous system, that develops independently from the central and peripheral nervous systems, and which is responsible for intestinal motility. Moreover, it receives extensive sympathetic and parasympathetic innervation, which controls intestinal secretions and motility [97][98][99][100] . While digestion in the upper tract is mostly mechanical and enzymatic, in the lower tract, bacterial fermentation is necessary for finishing the process, particularly for breaking down complex carbohydrates through fermentation, as well as for synthesizing micronutrients such as B vitamins and vitamin K 101,102 .…”
Section: An Unusual Candidate -The Gut Microbiotamentioning
confidence: 99%